COVID-19 Pandemic and MSMEs: Impact and Mitigation - David Ronald Tairas (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2020)
Indonesia announced the first COVID-19 case in early of March 2020. Since then, the mobility restriction has hampered the economy, including the micro, small and medium enterprises (MSMEs) businesses. This study aims to explore the types of challenges encountered by MSMEs to sustain their businesses during the hardship. Descriptive qualitative method is used, with data sourced from interview with 34 MSMEs, one in each province in Indonesia, as well as secondary sources including research journals and various reports on the COVID-19 pandemic. The results show that business owners experience difficulties in producing goods and services because of the raw materials shortage, financial liquidity and decreasing demand. Policy and managerial implications of the study are provided.